MODELING OF NONLINEAR CHANGE OF RADIATION-MECHANICAL CHARACTERISTICS OF STEEL 45ХН2МФА AT TECHNOLOGICAL IRRADIATION WITH RELATIVISTIC ELECTRONS - Bytkin, Sergey; Krytskaya, Tatiana; Lytvynenko, Vladimir (Scientific Journal "Metallurgy", 2022)
A technique for processing experimental data (modeling of individual sections of the dose dependence using MathCAD and OriginPRO) was proposed for a clear description and prediction of the possibility of technological application of a flow of relativistic electrons with an energy of 5 MeV to increase the impact strength (KCU) of 45KhN2MFA. It was shown that the change in the radiation-mechanical properties is essentially nonlinear. With an increase in the radiation dose, several areas of change in the physical (radiation-mechanical) properties of rolled metal was observed.The obtained results were explained using generally accepted theoretical concepts. At radiation doses Фе ≤ 5·1014 cm-2 no significant changes in the physical properties of steel were observed. In the range 5·1014 < Фе ≤ 3·1015 см-2 the numerical value of σ0,2 was growing and KCU was decreasing, the rates of their change are opposite (have different signs with practical equality of amplitudes). The σB change rate in this interval was insignificant. At 4·1015 < Фе ≤ 4,5·1015 cm-2 the process of the impact strength reducing of the metal with an increase in its strength was expressed especially clearly. It seems that the process of KCU, σ0,2, σT change is associated with the interaction of point radiation defects (vacancies, prevailing in the conditions of thermal equilibrium) and impurity atmospheres of dislocations. Near the dislocation, there is a cluster of impurity atoms, fixed (segregated) on dislocations, forming the Cottrell atmosphere. Reducing the concentration of interstitial carbon surrounding the dislocation allows vacancies accumulating during irradiation to "dissolve" segregated impurities (not only carbon, but also alloying). The "explosive" nature of the KCU change at Фе 5·1015 см-2 and corresponding rapid change of σ0,2, σT suggest the separation of dislocations from the impurity atmosphere and the creation of conditions for the growth of toughness with an increase in the radiation dose.